2021
DOI: 10.1186/s41610-021-00207-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nocturnal insect communities in forest-dominated landscape relevant to artificial light intensity

Abstract: Background Artificial light at night has recently been identified as a major factor adversely affecting global insect diversity. Here, we compared the insect diversity in Gwangneung Forest Biosphere Reserve, specifically in the Korea National Arboretum (with no artificial light at night), with that of three nearby urban sites with a gradient of artificial light at night (five locations at each site). We analyzed the effects of the artificial night lighting index, mean annual temperature, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While global insect defaunation is thought to be partly a result of such mechanisms, the relationship between invertebrate abundance and ALAN is complex; evident in the mixed results of studies to date. While a recent study of terrestrial insects in hedgerows and grass margins found significantly lower abundance in habitats illuminated by streetlights than those not [12], further studies show correlations which are positive [13,14], species dependent [15][16][17] or non-significant [18]. Possible explanations include varying predation under ALAN.…”
Section: Introductionmentioning
confidence: 77%
“…While global insect defaunation is thought to be partly a result of such mechanisms, the relationship between invertebrate abundance and ALAN is complex; evident in the mixed results of studies to date. While a recent study of terrestrial insects in hedgerows and grass margins found significantly lower abundance in habitats illuminated by streetlights than those not [12], further studies show correlations which are positive [13,14], species dependent [15][16][17] or non-significant [18]. Possible explanations include varying predation under ALAN.…”
Section: Introductionmentioning
confidence: 77%
“…It has been suggested, for example, that the intrusion of light into otherwise dark night‐time environments disrupts insects' foraging behaviour (Cieraad et al, 2022; Tierney et al, 2017; van Langevelde et al, 2018) and decreases the nutritional bioavailability of their hostplants (Grenis & Murphy, 2019); but whether this ultimately affects herbivorous insect abundance is unclear. Some researchers have reported that, at broad scales, insects are less abundant near streetlighting (Boyes et al, 2021b), whilst others report abundance levels which are the same, species‐dependent, or greater near various forms of ALAN (Firebaugh & Haynes, 2020; Hakbong et al, 2021; Lockett et al, 2021; Manfrin et al, 2017; McMunn et al, 2019; Willmott et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies reported already changes in diet preferences in several bat species, including P. pipistrellus which also feed on Lepidoptera (Arlettaz et al, 2000;Rydell, 1992). As ALAN alters the assemblage compositions of invertebrates (Grubisic and van Grunsven, 2021;Hakbong et al, 2021), this could lead to cascading effects on the diet preferences of bats.…”
Section: Insect Abundancementioning
confidence: 99%